2020
DOI: 10.1080/22423982.2020.1787022
|View full text |Cite
|
Sign up to set email alerts
|

Persistent pain associated with socioeconomic and personal factors in a Sami and Non-Sami population in Norway: an analysis of SAMINOR 2 survey data

Abstract: In international studies, higher prevalence of persistent pain has been reported in indigenous populations compared to majority populations. The present study aimed to determine the prevalence of persistent pain within a Sami and a non-Sami population in northern Norway, with adjustment for the confounding factors of age, sex, marital status, education, income, mental health, smoking status and ethnic background. Using SAMINOR 2 survey data including Sami and non-Sami populations, we analysed 5,546 responses, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
(78 reference statements)
0
1
0
Order By: Relevance
“…Overall, studies on the prevalence of CMSP among the Sami compared with non-Sami living in the same geographic areas in Norway have found no or only minor differences [ 11–14 ]. Some studies found a higher prevalence of CMSP among the Sami for some pain sites [ 11–13 ], while another study found less CMSP for Sami women aged 60–79 years than non-Sami women in the same age group [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, studies on the prevalence of CMSP among the Sami compared with non-Sami living in the same geographic areas in Norway have found no or only minor differences [ 11–14 ]. Some studies found a higher prevalence of CMSP among the Sami for some pain sites [ 11–13 ], while another study found less CMSP for Sami women aged 60–79 years than non-Sami women in the same age group [ 15 ].…”
Section: Introductionmentioning
confidence: 99%